A General Survey of B.A.M.S. Students to Improve Overall Teaching (AYUSHDHARA, 2022)
For any professional course it is very important to identify students’ perceptions and suggestions to improve the system of education. To solve this purpose this study was planned by conducting a survey among the students of B.A.M.S. The current course of B.A.M.S. is the combination of ancient Ayurveda and modern medical science, where students find some difficulties to understand and co-relate it with real time patients. Google form was prepared to conduct this survey and it was filled up online by 352 students of seven different Ayurveda colleges of Saurashtra region, Gujarat. In this survey an effort has been made to know the background of students, their understanding about the course, certain generalized questions were also included in the questionnaire, i.e. professional goal after completion of B.A.M.S., what they think about the current teaching methodology and if they need any change in its different aspects or in syllabus. The result is found to be beyond our imagination, which is the best teaching pattern; chalk & board or digital platform. The impact of online education has become the new opportunity for students to indulge themselves in more usage of mobile or electronic gadgets in the name of educational purpose.